(untitled) (Bangladesh Journal of Medical Physics, 2013)
Breast cancer is one of the most common diseases affecting women and the mortality rate is very high in Bangladesh, mainly due to the lack of early diagnosis. X-ray mammography is not available widely in Bangladesh, besides it has an associated biological hazard. Multi-frequency bio-impedance measurement or bio-impedance spectroscopy has a great potential in many biomedical applications including breast cancer screening which involves tissue characterization. In Bio-impedance spectroscopy a range of frequencies of low level current is injected to the human body and corresponding bio-impedance is measured. In a typical bio-impedance measurement system an ac source with a constant current amplitude is an essential part in which the current amplitude should not change with frequency or load, the latter being typically of the order of a few kilo ohms in the human body. The constant current source is usually obtained from a voltage-to-current converter and several standard designs are available, for example a floating current source, a Howland current source and an enhanced Howland current source. The present work was taken up to perform a comparative study of these three types of current sources based on a commonly available low cost operational amplifier, 741. It was found that the enhanced Howland current source gave the best performance, the current being almost constant up to a frequency of about 10kHz for a load of 10k?. This work gives an understanding of this fundamental circuit segment that is essential for the development of a Bioimpedance Spectroscopy system. DOI: http://dx.doi.org/10.3329/bjmp.v5i1.14671 Bangladesh Journal of Medical Physics Vol.5 No.1 2012 71-76